2021
DOI: 10.1002/aic.17174
|View full text |Cite
|
Sign up to set email alerts
|

Rapid multi‐component phase‐split calculations using volume functions and reduction methods

Abstract: We present a new family of fast and robust methods for the calculation of the vapor-liquid equilibrium at isobaric-isothermal (PT-flash), isochoric-isothermal (VT-flash), isenthalpic-isobaric (HP-flash), and isoenergetic-isochoric (UV-flash) conditions. The framework is provided by formulating phase-equilibrium conditions for multi-component mixtures in an effectively reduced space based on the molar specific value of the recently introduced volume function derived from the Helmholtz free energy. The proposed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To solve the VLE equations, we utilize the newly introduced method of Fathi and Hickel [3] that performs UV-flash calculations very fast and robust via Newton iterations with the exact Jacobian based on an effective reduction method. We note that tabulation methods are a suitable alternative for non-reacting flows.…”
Section: Flash Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the VLE equations, we utilize the newly introduced method of Fathi and Hickel [3] that performs UV-flash calculations very fast and robust via Newton iterations with the exact Jacobian based on an effective reduction method. We note that tabulation methods are a suitable alternative for non-reacting flows.…”
Section: Flash Calculationsmentioning
confidence: 99%
“…For a comprehensive review and practical implementation guidelines, readers are referred to Ref. [3].…”
Section: Flash Calculationsmentioning
confidence: 99%
“…As for PHN stability, no detailed analysis was provided in the literature. UVN (isochoric-isoenergetic) phase equilibrium (consisting of the maximization of entropy at given internal energy, volume and moles) [1][2][3][51][52][53][54][55][56][57] is applied in rigorous dynamic simulation of distillation columns; simulating two-phase pipe flow, filling tank, venting and leaks from pressure vessels, etc. A derivation of the TPD function at UVN conditions was apparently first given by Castier [52], who also showed that a PT stability testing can be carried out to assess UVN stability.…”
mentioning
confidence: 99%